A new strategy of desensitization in mucopolysaccharidosis type II disease treated with idursulfase therapy: A case report and review of the literature - Vincenza Gragnaniello; Silvia Carraro; Laura Rubert; Daniela Gueraldi; Chiara Cazzorla; Pamela Massa; Stefania Zanconato; Alberto B. Burlina (Molecular Genetics and Metabolism Reports, 2022)
Mucopolysaccharidosis type II (MPS II) is a multisystemic lysosomal storage disorder caused by deficiency of the iduronate 2-sulfatase enzyme. Currently, enzyme replacement therapy (ERT) with recombinant idursulfase is the main treatment available to decrease morbidity and improve quality of life. However, infusion-associated reactions (IARs) are reported and may limit access to treatment. When premedication or infusion rate reductions are ineffective for preventing IARs, desensitization can be applied. To date, only two MPS II patients are reported to have undergone desensitization. We report a pediatric patient with recurrent IARs during infusion successfully managed with gradual desensitization. Our protocol started at 50% of the standard dosage infused at concentrations from 0.0006 to 0.06 mg/ml on weeks 1 and 2, followed by 75% of the standard dosage infused at concentrations from 0.0009 to 0.09 mg/ml on weeks 3 and 4, and full standard dosage thereafter, infused at progressively increasing concentrations until the standard infusion conditions were reached at 3 months. Our experience can be used in the management of MPS II patients presenting IARs to idursulfase infusion, even when general preventive measures are already administered.